Study of antiviral activity of a new plant origin preparation neoflazidum on a model of the hepatitis C virus - Porva, Yu.I.; Rybalko, S.L.; Palchykovs’ka, L.I.; Atamanyuk, V.P. (Вiopolymers and Cell, 2015)
Aim. Investigation of antiviral activity of a new plant origin preparation – neoflazidum, a form of proteflazidum Methods. A model of hepatitis C virus-producing Jurkat cell culture (JurkatHCV) which has been previously transfected with complementary DNA preparations isolated from different types of hepatitis C virus (HCV). Results.To obtain these preparations, HCV RNA preparations were isolated from viral material of HCV-diseased patients, the transfecting agent Turbofect being used. The cytotoxic dose (CD50) was shown to be 37.2 μg/ml, the effective dose (ED50) being 0.46 μg/ml for the HCV type 3a; this dose, however, was as high as 3.7 μg/ml when neoflazidum had been tested for HCV type 1b. Therefore, the selectivity index for the HCV type 3a reached 80.8 in the JurkatHCV-3a cell system, being as low as 10.0 for the HCV type 1b. Conclusion. Using a model system RNAP T7, the antiviral neoflazidum activity was demonstrated to be realized due to interferons α- and γ-induction and RNA synthesis inhibition. Мета. Вивчення антивірусної активності нової форми рослинного екстракту Протефлазіду (РЕП) – Методи. Моделі продукуючої культури Jurkat кДНК ВГС. Результати. Одержані продукуючі ВГС культури клітин Jurkat методом трансфекції комплементарної ДНК до виділеної РНК ВГС від хворих гепатитом С за допомогою трансфекуючого реагента Turbofect. Цитотоксична доза (CD50) дорівнювала 37,2 мкг/мл, ефективна доза (ED50) в системі продукції вірусу гепатиту С 3а типу дорівнювала 2,3 мкг/мл, а в системі репродукції вірусу гепатиту С 1в типу – 18,6 мкг/мл. Тому індекс селективності для РЕП в системі продукуючих ВГС клітин 3а типу дорівнював 16,2, а для ВГС 1в типу – 2. Висновки. Механізм антивірусної дії РЕП відбувається за рахунок індукції α- та γ-інтерферону та інгібіції синтезу РНК в модельній системі РНКП Т7 – інгібуюча концентрація (IC50) – 0,78 мкг/мл. Цель. Изученить антивирусную активности новой формы растительного экстракта Протефлазида (РЭП). Методы. Модель продуцируемого культуры Jurkat кДНК ВГС. Результаты. Полученные продуцирующие ВГС культуры клеток Jurkat методом трансфекции комплементарной ДНК к выделенной РНК ВГС от больных гепатитом С с помощью трансфецирующего реагента Turbofect. Цитотоксическое доза (CD50) равнялась 37,2 мкг / мл, эффективная доза (ED50) в системе продукции вируса гепатита С 3а типа равна 2,3 мкг / мл, а в системе репродукции вируса гепатита С 1в типа – 18,6 мкг / мл. Поэтому индекс селективности для РЭП в системе продуцирующих ВГС клеток 3а типа равен 16,2, а для ВГС 1в типа – 2. Выводы. Механизм антивирусного действия РЭП происходит за счет индукции α- и γ-интерферона и ингибирования синтеза РНК в модельной системе РНКП Т7 – ингибирующая концентрация (IC50) – 0,78 мкг / мл.